(untitled) (Journal of the College of Education for Women, 2019)
Excerption and inclusion are two terms in Arabic rhetoric. The excerption is defined as a taking a part of text from Holly Quran or Hadith and put it in a poem, verse line, or put it in a prose text. But the linguistics expand the concept of this term to include taking from another sciences and knowledge, like Grammar, Philology, and Prosody.Inclusion is defined as taking a verse line or part of verse line from another poet to put it in a new poem, it is necessary that the poet who take the text should declare it, and if he hides it, it will be plagiarism.This search is use these two terms in architecture, we have now new two terms in architecture, first one; architectural excerption, it means the designer takes a part of religious or historical building and put it in his new design. The designer also can take from another sciences and knowledge, like physics, mathematics, or schools of modern criticism like deconstruction, to put his new design. The second term (architectural inclusion) means the designer takes a part of another modern design, neither religious nor historical, if he hides this, it is considered as architectural plagiarism.The search is proved that there are many architectural designs which include the meaning of these two terms.